Machine Vision Automated Visual Inspection: Theory, Practice and Applications - Beyerer, Jürgen; Puente León, Fernando; Frese, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
The book offers a thorough introduction to machine vision. It is organized in two parts. The first part covers the image acquisition, which is the crucial component of most automated visual inspection systems. All important methods are described in great detail and are presented with a reasoned structure. The second part deals with the modeling and processing of image signals and pays particular regard to methods, which are relevant for automated visual inspection.
Introduction -- Part I Image Acquisition: Light -- Optical Imaging -- Radiometry -- Color -- Sensors for Image Acquisition -- Methods for Image Acquisition -- Part II Image Processing: Image Signals -- Preprocessing and Image Enhancement -- Image Restoration -- Segmentation -- Morphological Image Processing -- Texture Analysis -- Detection -- Image Pyramids, Wavelet Transform and Multiresolution Analysis -- Mathematical Foundations -- The Fourier Transform.
Keywords: Signal processing; Computer vision; Control engineering; Robotics; Automation; Measurement; Measuring instruments; Signal, Speech and Image Processing .; Computer Vision; Control, Robotics, Automation; Measurement Science and Instrumentation